Purification method of disperse dye

By beating, ultrasonic or high-speed shear dispersion of the dispersed dye, combined with membrane desalting treatment, poor ink stability caused by inorganic salts and impurities in the dispersed dyes are solved, and the purification effect of dispersed dyes is achieved with high purity and stability.

CN119662047APending Publication Date: 2025-03-21TIANJIN JINGLI DIGITAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411833385.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing dispersed dyes contain high inorganic salts and impurities, resulting in poor ink stability and prone to problems such as oblique spraying, plugging and breakpoints of the nozzles. Purification is required to improve the purity of the dye.

Method used

Dispersed dye beating, ultrasonic dispersion, high-speed shear dispersion or grinding treatment is used, combined with membrane equipment for desalting treatment, and then concentrated and dispersant added for grinding until the desired particle size and purity are reached.

Benefits of technology

Through this method, the purity of the dispersed dye is significantly improved, the inorganic salt content is reduced, the nozzle corrosion is prevented, and the ink stability and printing and dyeing are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186089080000041
    Figure BDA0005186089080000041
  • Figure BDA0005186089080000051
    Figure BDA0005186089080000051
  • Figure BDA0005186089080000052
    Figure BDA0005186089080000052
Patent Text Reader

Abstract

The invention discloses a method for purifying a disperse dye, which comprises the following steps: S1, pulping the disperse dye; s2, performing ultrasonic dispersion and / or high-speed shearing dispersion on the pulped material, and / or grinding the pulped material; s3, carrying out desalination treatment on the material treated in the step S2; and S4, after desalination treatment, concentrating the disperse dye liquid until the concentration is 10-35%, then adding a dispersing agent, transferring into a grinding machine for grinding, and obtaining the purified disperse dye after detection is qualified. The disperse dye treated by the process is high in purity and low in salt content, meanwhile, compared with the prior art, the subsequent grinding time can be shortened, and the process can be suitable for preparing ink for ink-jet textile printing and dyeing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of disperse dyes, and in particular to a method for purifying disperse dyes, and application of the disperse dyes obtained after purification in textile printing and dyeing. Background Art

[0002] Disperse dyes are mainly used for dyeing (printing) of polyester and its textiles, and can be used for dyeing (printing) of acetate fiber and nylon fiber, and can also be used for transfer printing. At present, disperse dyes are of various varieties, with complete color spectrum, excellent performance and wide application, becoming the fastest growing type of dyes. With the rapid development of electronic computer technology. In recent years, people have applied paper inkjet printing technology to textile printing, advertising inkjet printing, clothing, etc. It has the advantages of short process, small batch and fast delivery, which has attracted wide attention in the printing and dyeing industry. In particular, with the continuous improvement of inkjet printing equipment and the decline in dye prices, this technology will be widely used. The purity requirement of dyes is very important. Because the solid content of the original disperse dye is generally 30% to 60%, the remaining ingredients include water, inorganic salts produced in the synthesis process, impurities in the dye during the synthesis process, etc., among which, when the dye is precipitated in the synthesis, a certain amount of inorganic salts in the solvent will be wrapped, resulting in this part of the inorganic salts in the particles cannot be removed, however, the inorganic salts and impurities in the dye will destroy the stability of the ink, resulting in problems such as oblique spraying, plugging, and breakpoints in the printer nozzle. Therefore, the original dye must be purified, the content of inorganic salts in the dye must be reduced, and other impurities must be removed. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for purifying disperse dyes.

[0004] The technical solution adopted by the present invention is:

[0005] First,

[0006] The present invention provides a method for purifying disperse dyes, comprising the following steps:

[0007] S1: disperse dye beating;

[0008] S2: ultrasonically dispersing the pulped material, and / or high-speed shearing dispersing, and / or grinding the pulped material;

[0009] S3: Desalting the material after the treatment in step S2;

[0010] S4: After desalting, the disperse dye liquid is concentrated to a concentration of 10-35%, and then a dispersant is added and transferred to a grinder for grinding. After being tested and qualified, the purified disperse dye is obtained.

[0011] In some embodiments, the disperse dye is one or more of disperse red, disperse yellow, disperse blue, disperse violet, and disperse orange.

[0012] In some embodiments, the disperse dye is one or more of CI Disperse Yellow 114, CI Disperse Red 343, CI Disperse Blue 60, CI Disperse Violet 93, CI Disperse Orange 288, and CI Disperse Blue 291:1.

[0013] In some embodiments, the disperse dye (step S1) is a powder or a filter cake.

[0014] In some embodiments, in step S1, the disperse dye pulping is to add water to the disperse dye for pulping, wherein the mass ratio of the disperse dye to water is 1:(2.5-9).

[0015] In some embodiments, in step S1, the disperse dye pulping is to add water to the disperse dye and then perform at least one of stirring dispersion and low-speed shear dispersion; wherein:

[0016] The conditions for stirring and dispersing are: stirring rate of 40-200 rpm, stirring time of 0.5-2 hours, and temperature of 20-40°C. Under this condition, the powder of disperse dye is fully mixed with water, which plays a role of pre-dispersion. It is found in the experiment that the stirring speed is lower than 40 rpm, and the dispersion effect is not achieved. When the stirring speed is higher than 200 rpm, the disperse dye is very light and tends to float on the water surface before being wetted by water. If the stirring speed is too fast, the particles are easy to float out, which affects the beating and dispersion effect.

[0017] The conditions for low-speed shear dispersion are: shear rate of 500 to 3000 rpm, temperature of 20 to 40° C., and time of 1 to 2 hours.

[0018] In the method of the present invention, in step S1, the powder of the disperse dye is fully mixed with water to play a role of pre-dispersion, and then the ultrasonic dispersion, and / or high-speed shear dispersion, and / or grinding treatment are carried out in step S2 to further disperse the particles, so that the particles are dispersed more evenly and the presence of large particles is reduced. The particles of the disperse dye are reopened and the inorganic salts encapsulated therein are redissolved in water. Compared with the inorganic salts in the particulate matter that exist in the form of adsorption or inclusion, the inorganic salts are more likely to exist in water due to solubility. Therefore, once the particles are opened, the inorganic salts tend to be more soluble in water. Regardless of whether the disperse dyes are re-aggregated, a low amount of inorganic salt encapsulation will be maintained.

[0019] In some embodiments, in step S2, the ultrasonic dispersion power is 180 W, the temperature is 20-40° C., and the time is 1-2 hours.

[0020] In some embodiments, in step S2, the rotation speed of the high-speed shear dispersion is 9000 to 20000 rpm, and the time is 1 to 2 hours.

[0021] In some embodiments, in step S2, the grinding conditions are grinding to a particle size less than 500 nm; specifically, the grinding speed is a linear speed of 12 to 14 m / s; the grinding temperature is 20 to 35° C., and the grinding time is 1 to 2 hours.

[0022] In some preferred embodiments, in step S2, ultrasonic dispersion is first performed, the ultrasonic power is 180W, the temperature is 20-40°C, and the time is 1-2 hours; and then grinding is performed, the grinding line speed is 12-14 m / s, the grinding temperature is 20-35°C, and the grinding time is 1-2 hours. In this process, the ultrasonic equipment further reduces the particle size of disperse dyes, especially particularly large particles, by vibration. During the particle size reduction process, the wrapped inorganic salt gradually dissolves in water, and then grinds in the grinding equipment for 1-2 hours. At this time, the particle size of the system is ground by zirconium beads, and the particle size is smaller. During the particle size reduction process, the inorganic salt is further gradually released.

[0023] In some embodiments, in step S3, the desalination treatment includes: firstly using a microfiltration membrane for pretreatment before desalination, and then performing desalination;

[0024] The microfiltration membrane is in the form of a flat membrane, a hollow fiber membrane or a ceramic membrane; the pore size is 1 to 10 microns; the inlet pressure is 0.2 to 2 MPa;

[0025] The membrane used for desalination is a tubular ceramic membrane or a flat ceramic membrane; the pore size is 10 to 50 nm; the inlet pressure is 0.2 to 0.6 MPa.

[0026] In some embodiments, in step S3, the concentration is performed using a ceramic membrane.

[0027] In some embodiments, in step S4, the dispersant is at least one of naphthalene sulfonate and methyl naphthalene sulfonate formaldehyde condensate; and the amount of the dispersant added is 10-30% based on the mass of the disperse dye.

[0028] In some embodiments, in step S4, the grinding conditions are grinding to a particle size of 80 to 150 nm; specifically, the grinding speed is 12 to 14 m / s; the grinding temperature is 20 to 35° C., and the grinding time is 2 to 5 hours.

[0029] In some embodiments, in step S4, the grinding time is 2 to 4 hours.

[0030] In some embodiments, in step S4, the grinding time is 2 to 3 hours.

[0031] In some embodiments, in step S4, the qualified detection means that the particle size of the disperse dye is between 80 and 150 nm.

[0032] The embodiment of the present invention also provides a disperse dye purified product, which is prepared by the above purification method.

[0033] Thirdly,

[0034] The embodiment of the present invention also provides the use of the above-mentioned disperse dye purified product in textile printing and dyeing.

[0035] The disperse dye purification product is used for digital inkjet textile printing and dyeing.

[0036] Fourthly,

[0037] The embodiment of the present invention further provides an ink, wherein the raw material of the ink includes the above-mentioned disperse dye purified material.

[0038] In some embodiments, the pH of the ink is 6 to 8.5.

[0039] In some embodiments, the ink comprises the following raw materials in parts by weight: 4 to 8 parts of disperse dye (dry product), 60 to 70 parts of water, 25 to 35 parts of alcohol, 0.1 to 0.5 parts of pH adjuster, and 0.1 to 0.5 parts of preservative.

[0040] In some embodiments, the alcohol is at least one of ethylene glycol, 1,2-propylene glycol, and glycerol; the pH adjuster is at least one of triethanolamine, diethanolamine, ethanolamine, sodium bicarbonate, sodium hydroxide, sodium carbonate, sodium acetate, and ammonium bicarbonate; and the preservative is at least one of BIT, CMIT, and MIT.

[0041] The advantages and beneficial effects of the embodiments of the present invention are as follows:

[0042] The embodiment of the present invention provides a method for purifying disperse dyes, wherein the disperse dyes are beaten, the beaten materials are ultrasonically dispersed, and / or high-speed shear dispersed, and / or the beaten materials are ground, and the dispersed materials are desalted using a membrane device. The disperse dyes treated by the process have high purity and low salt content, and compared with the prior art, the subsequent grinding time can be reduced, and the process can be applied to the preparation of inkjet textile printing inks. Because the salt content is low, the corrosion of the nozzle of the inkjet printing device can be prevented, and the obtained disperse dye paste and ink have good stability, the difference between batches is reduced, and the printing and dyeing consistency is good. DETAILED DESCRIPTION

[0043] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0044] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0045] Where values ​​are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values ​​falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.

[0046] In this document, in the "first aspect", "second aspect", "third aspect", etc., the terms "first", "second", "third", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0047] In this document, references to “preferred”, “more preferred” and “better” are merely intended to describe implementation methods or examples with better effects, and should be understood that they do not limit the scope of protection of the present invention.

[0048] In this document, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0049] In this article, the term "and / or" is a description of the association relationship of objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or A and B.

[0050] The following are specific embodiments and comparative examples of the present invention. It should be further explained that the following comparative examples are not prior art and are only provided for comparison with the embodiments and are not intended to limit the present invention.

[0051] In the embodiment of the present invention, the structure of the disperse dye involved is as follows

[0052] CI Disperse Yellow 114

[0053]

[0054] CI Disperse Red 343

[0055]

[0056] CI Disperse Blue 60

[0057]

[0058] CI Disperse Violet 93

[0059]

[0060] CI Disperse Orange 288

[0061]

[0062] CI Disperse Blue 291:1

[0063]

[0064] In the embodiments of the present invention and the comparative examples:

[0065] dye:

[0066] CI Disperse Red 343 dye, purchased from: Foshan Huangwei Trading Co., Ltd.

[0067] CI Disperse Blue 60 dye, purchased from: Boao Chemical Co., Ltd.

[0068] CI Disperse Yellow 114 dye, purchased from: Jiangsu Shengji Chemical Co., Ltd.

[0069] CI Disperse Violet 93 dye, purchased from: Jiangsu Shengji Chemical Co., Ltd.

[0070] CI Disperse Orange 288 dye, purchased from: Jiangsu Shengji Chemical Co., Ltd.

[0071] CI Disperse Blue 291:1 dye, purchased from: Jiangsu Shengji Chemical Co., Ltd.

[0072] equipment:

[0073] Ceramic membrane, purchased from: Jiangsu Jiuwu High-Tech Co., Ltd.; ceramic membrane equipment (model CeraMem0100), Xiamen Fumei Technology Co., Ltd.

[0074] Hollow fiber membrane, purchased from: Tianjin Dingxin Membrane Technology Co., Ltd., membrane equipment, self-assembled.

[0075] Flat membrane, purchased from: Zhongke Ruiyang (Beijing) Co., Ltd., flat membrane equipment (FlowMem-0021-HP), Xiamen Fumei Technology Co., Ltd.

[0076] In the examples and comparative examples of the present application, if no specific temperature conditions are specified, they are all carried out at room temperature.

[0077] Example 1

[0078] A method for purifying disperse dyes comprises the following steps:

[0079] S1: Take 50 g of commercially available CI Disperse Red 343 dye, add 350 ml of purified water, and beat with a stirrer for 1 hour at a stirring rate of 80 rpm;

[0080] S2: The obtained pulped material was dispersed by ultrasonic disperser for 1 hour, the ultrasonic power was 180W, and the obtained dispersion was sampled and tested for ion content (the results are shown in Table 1);

[0081] S3: Pre-treatment with microfiltration membrane (ceramic membrane), the membrane pore size is 1 micron, the inlet pressure is 1MPa, and then desalination with tubular ceramic membrane, the membrane pore size is 30nm, the inlet pressure is 0.5MPa. Remove free inorganic salts and some small molecular impurities;

[0082] S4: Use ceramic membrane to concentrate until the concentration is 30%, add 5 grams of naphthalenesulfonate dispersant, transfer to a grinder for grinding, and the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 5 hours, and after the particle size test is qualified, a dispersed red color paste is obtained.

[0083] Example 2

[0084] A method for purifying disperse dyes comprises the following steps:

[0085] S1: Take 50 g of commercially available CI Disperse Red 343 dye, add 350 ml of purified water, and beat with a stirrer for 1 hour at a stirring rate of 80 rpm;

[0086] S2: The obtained pulped material was ground and dispersed with a grinder for 1 hour at a linear speed of 12 m / s, and the obtained dispersion was sampled and tested for ion content (the results are shown in Table 1);

[0087] S3: Pre-treatment with microfiltration membrane (hollow fiber membrane), membrane pore size of 5 microns, inlet pressure of 1 MPa, desalination with tubular ceramic membrane, membrane pore size of 50 nm, inlet pressure of 0.3 MPa. Remove free inorganic salts and some small molecular impurities;

[0088] S4: Use ceramic membrane to concentrate until the concentration is 28%, add 8 grams of naphthalenesulfonate dispersant, transfer to a grinder for grinding, and the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 5 hours, and after the particle size test is qualified, a dispersed red color paste is obtained.

[0089] Example 3

[0090] A method for purifying disperse dyes comprises the following steps:

[0091] S1: Take 100 g of commercially available CI Disperse Red 343 dye, add 500 ml of purified water, and beat with a stirrer for 1 hour at a stirring rate of 50 rpm;

[0092] S2: The obtained pulped material was dispersed for 1 hour using a high-speed dispersing shearing machine, the speed of the shearing machine was 12000 rpm, and the obtained dispersion was sampled and tested for ion content (the results are shown in Table 1);

[0093] S3: Pre-treatment with microfiltration membrane (flat membrane), membrane pore size of 5 microns, inlet pressure of 1 MPa, desalination with tubular ceramic membrane, membrane pore size of 50 nm, inlet pressure of 0.6 MPa. Remove free inorganic salts and some small molecular impurities;

[0094] S4: Use ceramic membrane to concentrate until the concentration is 33%, add 20 grams of naphthalenesulfonate dispersant, transfer to a grinder for grinding, and the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 4 hours, and after the particle size test is qualified, a dispersed red color paste is obtained.

[0095] Example 4

[0096] A method for purifying disperse dyes comprises the following steps:

[0097] S1: Take 80 g of commercially available CI Disperse Red 343 dye, add 400 ml of purified water, and beat with a stirrer for 0.5 hour at a stirring rate of 60 rpm;

[0098] S2: The obtained material was sheared with a shearing machine for 1 hour at a shearing speed of 10,000 rpm; the obtained material was ground with a grinder for 2 hours at a rotation speed of 12 m / s, and the obtained dispersion was sampled and tested for ion content (the results are shown in Table 1);

[0099] S3: Pre-treatment with microfiltration membrane (hollow fiber membrane), membrane pore size of 1 micron, inlet pressure of 0.8 MPa, desalination with tubular ceramic membrane, membrane pore size of 50 nm, inlet pressure of 0.5 MPa. Remove free inorganic salts and some small molecular impurities;

[0100] S4: Use ceramic membrane to concentrate until the concentration is 30%, add 15 grams of naphthalenesulfonate dispersant, transfer to a grinder for grinding, and the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 3 hours, and after the particle size test is qualified, a dispersed red color paste is obtained.

[0101] Example 5

[0102] A method for purifying disperse dyes comprises the following steps:

[0103] S1: Take 50 g of commercially available CI Disperse Red 343 dye, add 200 ml of purified water, and beat with a stirrer for 0.5 hour at a stirring rate of 50 rpm;

[0104] S2: The obtained pulped material was dispersed with an ultrasonic machine for 1 hour, and the ultrasonic power was 180W. The material obtained after ultrasonic dispersion was ground with a grinder for 2 hours, and the speed of the grinder was 12 m / s. The obtained dispersion was sampled and tested for ion content (the results are shown in Table 1);

[0105] S3: Pre-treatment with microfiltration membrane (ceramic membrane), the membrane pore size is 1 micron, the inlet pressure is 0.8 MPa, and desalination with tubular ceramic membrane, the membrane pore size is 30 nm, the inlet pressure is 0.5 MPa. Remove free inorganic salts and some small molecular impurities;

[0106] S4: Use ceramic membrane to concentrate until the concentration is 28%, add 15 grams of methyl naphthalene sulfonate formaldehyde condensate dispersant, transfer to a grinder for grinding, and the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 3 hours, and after the particle size test is qualified, a disperse red color paste is obtained.

[0107] Example 6

[0108] A method for purifying disperse dyes comprises the following steps:

[0109] S1: Take 50 g of commercially available CI Disperse Blue 60 dye, add 300 ml of purified water, and beat with a stirrer for 0.5 hour at a stirring rate of 50 rpm;

[0110] S2: The obtained pulped material was dispersed with an ultrasonic machine for 1 hour, and the ultrasonic power was 180W. The material obtained after ultrasonic dispersion was ground with a grinder for 2 hours, and the speed of the grinder was 12 m / s. The obtained dispersion was sampled and tested for ion content (the results are shown in Table 1);

[0111] S3: Pre-treatment with microfiltration membrane (hollow fiber membrane), membrane pore size is 5 microns, inlet pressure is 1MPa, desalination with tubular ceramic membrane, membrane pore size is 50nm, inlet pressure is 0.6MPa. Remove free inorganic salts and some small molecular impurities;

[0112] S4: Use ceramic membrane to concentrate until the concentration is 20%, add 10 grams of methyl naphthalene sulfonate formaldehyde condensate dispersant, transfer to a grinder for grinding, and the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 3 hours, and after the particle size test is qualified, a disperse blue color paste is obtained.

[0113] Example 7

[0114] A method for purifying disperse dyes comprises the following steps:

[0115] S1: Take 100 g of commercially available CI Disperse Yellow 114 dye, add 600 ml of purified water, and beat with a stirrer for 1 hour at a stirring rate of 60 rpm;

[0116] S2: The obtained pulped material was dispersed with an ultrasonic machine for 2 hours at an ultrasonic power of 180 W. The material obtained after ultrasonic dispersion was sheared with a high-speed shearing machine for 1 hour at a shear rate of 20,000 rpm. The obtained dispersion was sampled and tested for ion content (the results are shown in Table 1);

[0117] S3: Pre-treatment with microfiltration membrane (hollow fiber membrane), membrane pore size is 5 microns, inlet pressure is 1MPa, desalination with tubular ceramic membrane, membrane pore size is 50nm, inlet pressure is 0.4MPa. Remove free inorganic salts and some small molecular impurities;

[0118] S4: Use ceramic membrane to concentrate until the concentration is 25%, add 30 grams of naphthalenesulfonate dispersant, transfer to a grinder for grinding, and the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 2 hours, and after the particle size test is qualified, a dispersed yellow color paste is obtained.

[0119] Example 8

[0120] A method for purifying disperse dyes comprises the following steps:

[0121] S1: Take 70 g of commercially available CI Disperse Violet 93 dye, add 450 ml of purified water, and beat with a stirrer for 1 hour at a stirring rate of 50 rpm;

[0122] S2: The obtained pulped material was sheared for 2 hours using a high-speed shearing machine at a shear rate of 20,000 rpm, and the obtained dispersion was sampled and tested for ion content (the results are shown in Table 1);

[0123] S3: Pre-treatment with microfiltration membrane (hollow fiber membrane), membrane pore size is 1 micron, inlet pressure is 1 MPa, desalination with tubular ceramic membrane, membrane pore size is 50 nm, inlet pressure is 0.5 MPa. Remove free inorganic salts and some small molecular impurities;

[0124] S4: Use ceramic membrane to concentrate until the concentration is 30%, add 18 grams of naphthalenesulfonate dispersant, transfer to a grinder for grinding, and the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 2 hours, and after the particle size test is qualified, a dispersed purple color paste is obtained.

[0125] Comparative Example 1

[0126] Take 50 grams of commercially available disperse red 343 dye, add 350 milliliters of pure water, add 15% (based on the amount of dye) of the dispersant naphthalene sulfonate, use a shearing machine to beat for 2 hours, the shearing machine speed is 700 rpm, the sheared pulped material is sampled and tested for ion content (the results are shown in Table 1), and then transferred to a grinder and ground for 12 hours. When the average particle size is reduced to 80-150 nanometers, the disperse red color paste is obtained after the particle size test is qualified.

[0127] Comparative Example 2

[0128] Get 50 grams of commercially available product CI Disperse Red 343 dyestuff, add 350 milliliters of pure water, with agitator making beating 1 hour, stir speed (S.S.) is 50 rev / mins, with the dispersion liquid sampling test ion content (the results are shown in Table 1) that obtains, first use microfiltration membrane (hollow fiber membrane) to carry out the pre-treatment before desalination, membrane pore size is 1 micron, and inlet pressure is 1MPa, carry out desalination with tubular ceramic membrane again, membrane pore size is 50 nanometers, and membrane inlet pressure is 0.6MPa.Remove free inorganic salt and some small molecular impurities, adopt ceramic membrane to concentrate, until 30% concentration, add 5 grams of naphthalenesulfonate dispersants, change over to grinder and grind, grinding condition is: linear velocity 12 meters / second, when average grain size is reduced to 100-150 nanometer, grinding time is about 6 hours, and particle size detects the color paste that obtains disperse red after qualified.

[0129] Comparative Example 3

[0130] Take 50 grams of CI disperse blue 60 dye, a commercial product, add 300 milliliters of pure water, beat with a stirrer for 0.5 hours, the stirring rate is 50 rpm, the beaten material is dispersed with an ultrasonic machine for 15 minutes, the material obtained after ultrasonic dispersion is ground with a grinder for 0.5 hours, the rotation speed of the grinder is 12 meters per second, the obtained dispersion is sampled and tested for ion content (the results are shown in Table 1), and pre-treatment before desalination is performed with a microfiltration membrane (hollow fiber membrane), the membrane pore size is 1 micron, the inlet pressure is 1MPa, and then desalination is performed with a tubular ceramic membrane, the membrane pore size is 50nm, and the inlet pressure is 0.5MPa. Remove free inorganic salts and some small molecular impurities, use ceramic membrane concentration until the concentration is 20%, add 10 grams of methyl naphthalene sulfonate formaldehyde condensate dispersant and transfer to the grinder for grinding, the grinding condition is a linear speed of 12 meters per second; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 4 hours, and the disperse blue color paste is obtained after the particle size test is qualified.

[0131] Comparative Example 4

[0132] Take 50 grams of commercially available CI disperse blue 60 dye, add 300 ml of pure water, and beat with a stirrer for 2 hours at a stirring rate of 200 rpm. The beaten material is dispersed with an ultrasonic machine for 5 hours at an ultrasonic power of 180 W. The material obtained after ultrasonic dispersion is ground with a grinder for 6 hours at a speed of 12 m / s. The obtained dispersion is sampled and tested for ion content (the results are shown in Table 1). A microfiltration membrane (hollow fiber membrane) is used for pretreatment before desalination, with a membrane pore size of 5 microns and an inlet pressure of 2 MPa. A tubular ceramic membrane is used for desalination treatment, with a membrane pore size of 30 nm and an inlet pressure of 0.5 MPa. Remove free inorganic salts and some small molecular impurities, use ceramic membrane to concentrate until the concentration is 20%, add 10 grams of methyl naphthalene sulfonate formaldehyde condensate dispersant and transfer to grinder for grinding, the grinding condition is line speed 12 m / s; when the average particle size is reduced to 100-150 nanometers, the grinding time is about 4 hours, and dispersed blue color paste is obtained after the particle size test is qualified. Because the ultrasonic time and grinding time of this process are too long, the particle size becomes smaller in this process, and some material will be lost in the subsequent membrane treatment stage.

[0133] experiment:

[0134] (1) Ion test,

[0135] The disperse dye pastes obtained in the above examples and comparative examples were subjected to ion testing, and the results are shown in Table 1.

[0136] Table 1 Ion test results

[0137] <![CDATA[Ca 2+ (ppm)]]> <![CDATA[Na + (ppm)]]> <![CDATA[Mg 2+ (ppm)]]> <![CDATA[Cl - (ppm)]]> <![CDATA[SO 4 2- (ppm)]]> Example 1 413 1213 72.6 2566 411.8 Example 2 428 1257 65 2615 419 Example 3 410 1292 71.5 2594 424 Example 4 520 1451 85 2859 487 Example 5 527 1507 91 2911 492 Example 6 325 1523 16.4 3018 142 Example 7 382 2213 187 3502 1167 Example 8 259 805 148 1423 594 Comparative Example 1 54.5 205 6 417 33.9 Comparative Example 2 64 256 8 452 42 Comparative Example 3 104 416 13.5 821 68 Comparative Example 4 398 1307 85.4 2615 455

[0138] Through the ion test results of Examples 1-8, it can be seen that after the disperse dye is subjected to pretreatment of stirring and beating or low-speed shear dispersion, and then ultrasonic dispersion, and / or high-speed shear dispersion, and / or grinding of the pulped material, and then ion chromatography test, it is found that the ion content generally increases a lot, because after grinding, high-speed shearing or ultrasonic dispersion, or combined dispersion, the particles are reopened in this process, and after the particles are opened, the ions wrapped in the particles will be redissolved in water, although the subsequent particles may re-aggregate, but because the ions have been dissolved in water, the concentration of the ions has been diluted, and the content of the re-wrapped ions is relatively low. After the membrane treatment, the content of free ions is reduced a lot. Then the membrane treatment is used to remove the ions, so that the ion content in the disperse dye is greatly reduced.

[0139] Examples 1-5 and Comparative Examples 1-2 are for the same disperse red 343 dye. Comparative Examples 1-2 show that after the disperse dye is pulped in a common manner, the ion content in the test material is at a relatively low value, while after the method used in Examples 1-5, the measured ion content is 4-10 times higher than that of the comparative example. In addition, in Example 5, the effect of first performing ultrasonic dispersion and then grinding in step S2 is the best.

[0140] Example 6 (ultrasound for 1 hour and grinding for 2 hours in step S2) and comparative examples 3 and 4 are all for the same disperse blue 60 dye. By comparison, it can be seen that the disperse dye is slurried with pure water and the time of ultrasonic grinding is short (ultrasound for 15 minutes and grinding for 0.5 hours in step S2), and the content of the tested ions is low. It can be seen that the processing time is too short, the particles are not fully opened, and the wrapped ions are not fully released. In comparative example 4, the ultrasonic grinding time is too long (ultrasound for 5 hours and grinding for 6 hours in step S2), the tested ion content does not increase significantly, and the particles of the material are excessively reduced. When the next membrane treatment is carried out, a part of the material will be lost in the desalination process.

[0141] (2) Printing test

[0142] The printing test was conducted using the printer Epson R1390. The inks were prepared according to the ink ratios in Table 2. After the materials were mixed and stirred evenly, they were filtered using a membrane filter (pore size 1 μm) to prepare the inks. The storage stability (aging stability, filtration stability) of the prepared inks was then tested and evaluated.

[0143] Table 2 Ink Ratio

[0144] Ink composition content Disperse dyes 5% Ethylene glycol 20% Propylene glycol 10% Triethanolamine 0.3% BIT 0.2% water 64.5%

[0145] Aging stability:

[0146] Ink aging means: putting the ink into a sealed bottle and heating it in a 60℃ oven for one week.

[0147] The concentration after aging is tested using an ultraviolet spectrophotometer. The aged material is placed at room temperature. After the aged packaging bottle is opened, the upper and lower materials are sucked with a straw, and the same weight of materials are weighed, diluted to a certain concentration, and tested with an ultraviolet spectrophotometer to calculate the concentration difference between the upper and lower layers. Note: Examples 1-5 and Comparative Examples 1-2 are all Disperse Red 343, so inks with the same concentration are prepared for aging. The initial concentration of the dispersed red ink is 7.4%; Example 6 and Comparative Examples 3-4 are all Disperse Blue 60, and the initial concentration of the dispersed blue ink is 5.4%; Example 7 is Disperse Yellow 114, and the initial concentration of the dispersed yellow ink is 3.8%, and Example 8 is Disperse Violet 93, and the initial concentration of the dispersed violet ink is 4.5%; the calculation formula for the change rate of the concentration of the upper and lower layers after aging = (lower layer concentration after aging-upper layer concentration after aging) * 100% / initial concentration of the ink; the results are shown in Table 3.

[0148] Table 3 Concentration and concentration difference of upper and lower layers before and after ink aging

[0149] Upper layer concentration after aging Lower layer concentration after aging Concentration difference between upper and lower layers after aging Example 1 7.32 7.41 1.2% Example 2 7.36 7.43 1% Example 3 7.30 7.43 1.75% Example 4 7.36 7.42 0.81% Example 5 7.38 7.42 0.54% Example 6 5.37 5.43 1.11% Example 7 3.78 3.81 0.78% Example 8 4.48 4.52 0.89% Comparative Example 1 7.25 7.51 3.5% Comparative Example 2 7.20 7.52 4.32% Comparative Example 3 5.29 5.51 4.07% Comparative Example 4 5.35 5.46 2.03%

[0150] It can be seen from Table 3 that in Examples 1-8, after aging, the concentration difference between the upper and lower layers of the ink is relatively small, indicating that the disperse dyes purified by the purification method of the present invention are more stable and less likely to precipitate.

[0151] Example 1-5 and Comparative Example 1-2 are for the same disperse red 343 dye. After aging, the concentration difference between the upper and lower layers of Example 1-5 is less than 2%, while that of Comparative Examples 1 and 2 is greater than 3%. The effect of Example 1-5 is significantly better than that of Comparative Example 1-2, and the concentration difference between the upper and lower layers of Example 5 after aging is the smallest, which is 0.54%, and its effect is the best.

[0152] Example 6 (ultrasound for 1 hour and grinding for 2 hours in step S2) and comparative examples 3 and 4 are all for the same disperse blue 60 dye. By comparison, it can be seen that the time for pulping the disperse dye with pure water and ultrasonic grinding is relatively short (ultrasound for 15 minutes and grinding for 0.5 hour in step S2), and the concentration difference between the upper and lower layers after aging is 4.07%, and the effect is poor. In comparative example 4, the ultrasonic grinding time is too long (ultrasound for 5 hours and grinding for 6 hours in step S2), and the processing time is extended, but the concentration difference between the upper and lower layers after aging is 2.03%, which is significantly greater than 1.11% of Example 6. It can be seen that although the processing time of comparative example 4 is extended, the prepared ink is not as stable as that of Example 6.

[0153] Filtration stability: Test of filtration time: let the aged material stand at room temperature, take 1L of the material before and after aging respectively, use a polypropylene membrane with a diameter of 46mm and a pore size of 0.45 microns, and the vacuum degree during filtration is 0.08MPa. Record the filtration time of the material before and after aging respectively. The results are shown in Table 4.

[0154] Table 4 Filtration time and filtration time difference of materials before and after aging

[0155] Filtration time before aging Filtration time after aging Filtration time difference before and after aging Example 1 13′12″ 13′25″ 13″ Example 2 13′15″ 13′30″ 15″ Example 3 13′16″ 13′32″ 15″ Example 4 13′10″ 13′18″ 8″ Example 5 13′11″ 13′18″ 7″ Example 6 12′27″ 12′43″ 16″ Example 7 10′26″ 10′41″ 15″ Example 8 11′38″ 11′51″ 13″ Comparative Example 1 13′30″ 14′20″ 50″ Comparative Example 2 13′34″ 14′32″ 58″ Comparative Example 3 12′38″ 13′41″ 63″ Comparative Example 4 12′25″ 12′58″ 33″

[0156] It can be seen from Table 4 that in Examples 1-8, the filtration time increases slightly before and after the ink is aged, but the filtration time of the comparative ink increases significantly after aging. The reason for this is that since the content of inorganic salts in the comparative system is greater than that in the embodiment, the particles are partially aggregated. Compared with the embodiment system, large particles are precipitated in the comparative system, which are blocked on the membrane during filtration, resulting in an increase in the filtration time.

[0157] (3) Particle size test: The aged material is allowed to stand at room temperature, and the material before and after aging is taken respectively. The material before and after aging is tested with a particle size analyzer, and the increase in particle size D90 is recorded.

[0158] Table 5 Particle size D90 and its growth rate before and after aging

[0159]

[0160]

[0161] It can be seen from Table 5 that in Examples 1-8, the D90 particle size changes very little after aging, at about 5 nanometers, while the particle size of the ink prepared in Comparative Examples 1-4 increases by more than 10 nanometers after aging, indicating that during aging, since the content of inorganic salt in the comparative example system is greater than that in the example, the particles partially aggregate, resulting in a significant increase in the ink particle size.

[0162] (4) Viscosity test: The aged material was allowed to stand at room temperature, and the material before and after aging was taken to test the change in viscosity of the material before and after aging using a viscometer. The results are shown in Table 6.

[0163] Table 6 Viscosity and viscosity difference of materials before and after aging

[0164] Viscosity before aging (cP) Viscosity after aging (cP) Viscosity difference before and after aging Example 1 6.2 6.1 0.1 Example 2 6.17 6.04 0.13 Example 3 6.15 6.07 0.08 Example 4 6.22 6.11 0.11 Example 5 6.18 6.12 0.06 Example 6 6.1 6.01 0.09 Example 7 5.8 5.72 0.08 Example 8 5.97 5.91 0.06 Comparative Example 1 6.22 5.91 0.31 Comparative Example 2 6.25 5.90 0.35 Comparative Example 3 6.12 5.75 0.37 Comparative Example 4 6.24 6.12 0.12

[0165] It can be seen from Table 6 that Examples 1-5 and Comparative Examples 1-2 are for the same Disperse Red 343 dye, and the viscosity difference before and after aging of Examples 1-5 is less than 0.15 cP, while Comparative Examples 1 and 2 are greater than 0.3 cP. The effect of Example 1-5 is significantly better than that of Comparative Examples 1-2, and the viscosity difference before and after aging of Example 5 is the smallest, which is 0.06 cP, and its effect is the best.

[0166] Example 6 (ultrasonication for 1 hour and grinding for 2 hours in step S2), Comparative Example 3 (ultrasonication for 15 minutes and grinding for 0.5 hour in step S2) and Comparative Example 4 (ultrasonication for 5 hours and grinding for 6 hours in step S2) are all aimed at the same disperse blue 60 dye. By comparison, it can be seen that the viscosity difference before and after aging in Example 6 is 0.09 cP, while the viscosity difference before and after aging in Comparative Example 3 is 0.37 cP; the viscosity difference before and after aging in Comparative Example 4 is 0.12 cP; compared with Comparative Examples 3 and 4, the system ink of Example 6 is more stable.

[0167] (5) Conductivity test: The aged material is allowed to stand at room temperature, and the material before and after aging is taken to test the change in conductivity of the material before and after aging using a conductivity meter.

[0168] Table 7 Conductivity and conductivity difference of materials before and after aging

[0169]

[0170] It can be seen from Table 7 that in Examples 1-8, the conductivity of the ink increases slightly after aging, while the conductivity in Comparative Examples 1-3 increases significantly. It can be seen that the ink system treated by the purification method of the present invention is more stable due to the reduction of inorganic salts, and the untreated ink has more inorganic salts in the system, which will increase the conductivity of the ink more and make the system more unstable.

[0171] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0172] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for purifying disperse dyes, characterized in that: The steps include: S1: disperse dye beating; S2: ultrasonically dispersing the pulped material, and / or high-speed shearing dispersing, and / or grinding the pulped material; S3: Desalting the material after the treatment in step S2; S4: After desalting, the disperse dye liquid is concentrated to a concentration of 10-35%, and then a dispersant is added and transferred to a grinder for grinding. After passing the test, the purified disperse dye is obtained.

2. A method for purifying disperse dyes according to claim 1, characterized in that, The disperse dye is one or more of disperse red, disperse yellow, disperse blue, disperse violet and disperse orange; Furthermore, the disperse dye is one or more of CI Disperse Yellow 114, CI Disperse Red 343, CI Disperse Blue 60, CI Disperse Violet 93, CI Disperse Orange 288, and CI Disperse Blue 291:

1. Furthermore, the disperse dye is in the form of powder or filter cake.

3. A method for purifying disperse dyes according to claim 1, characterized in that, In step S1, the disperse dye beating is to add water to the disperse dye for beating, wherein the mass ratio of the disperse dye to water is 1:(2.5-9); the disperse dye beating is to add water to the disperse dye and then perform at least one of stirring dispersion and low-speed shear dispersion.

4. A method for purifying disperse dyes according to claim 3, characterized in that, The stirring and dispersing conditions are: stirring rate of 40 to 200 rpm, stirring time of 0.5 to 2 hours, and temperature of 20 to 40°C; The conditions of the low-speed shear dispersion are: a shear rate of 500 to 3000 rpm, a temperature of 20 to 40° C., and a time of 1 to 2 hours.

5. A method for purifying disperse dyes according to claim 3, characterized in that, In step S2, the power of ultrasonic dispersion is 180W, the temperature is 20-40°C, and the time is 1-2 hours; In step S2, the rotation speed of high-speed shear dispersion is 9000 to 20000 rpm, and the time is 1 to 2 hours; In step S2, the grinding conditions are grinding to a particle size of less than 500 nm; further, the grinding speed is a linear speed of 12 to 14 m / s, a grinding temperature of 20 to 35° C., and a grinding time of 1 to 2 hours.

6. A method for purifying disperse dyes according to claim 5, characterized in that, In step S2, ultrasonic dispersion is first performed with an ultrasonic power of 180 W, a temperature of 20 to 40° C., and a time of 1 to 2 hours; and then grinding is performed with a grinding line speed of 12 to 14 m / s, a grinding temperature of 20 to 35° C., and a grinding time of 1 to 2 hours.

7. A method for purifying disperse dyes according to claim 5, characterized in that, In step S3, The desalination treatment comprises: firstly using a microfiltration membrane for pretreatment before desalination, and then performing desalination; The microfiltration membrane is in the form of a flat membrane, a hollow fiber membrane or a ceramic membrane; the pore size is 1 to 10 microns; the inlet pressure is 0.2 to 2 MPa; The membrane used for desalination is a tubular ceramic membrane or a flat ceramic membrane; the pore size is 10 to 50 nm; the inlet pressure is 0.2 to 0.6 MPa.

8. A method for purifying disperse dyes according to claim 7, characterized in that, In step S4, the dispersant is at least one of naphthalene sulfonate and methyl naphthalene sulfonate formaldehyde condensate; the amount of the dispersant added is 10 to 30% based on the mass of the disperse dye; In step S4, the grinding conditions are grinding to a particle size of 80 to 150 nm; further, the grinding speed is 12 to 14 m / s; the grinding temperature is 20 to 35° C., and the grinding time is 2 to 5 hours. In step S4, the qualified detection means that the particle size of the disperse dye is between 80 and 150 nm.

9. A disperse dye purified product, characterized in that: The product is prepared by the purification method described in any one of claims 1 to 8.

10. Use of the disperse dye purified product according to claim 9 in textile printing and dyeing, characterized in that: The disperse dye purification product is used for digital inkjet textile printing and dyeing; Furthermore, the disperse dye purified product is prepared into ink for digital inkjet textile printing and dyeing, and the ink comprises the following raw materials in parts by weight: 4 to 8 parts of disperse dye (dry product), 60 to 70 parts of water, 25 to 35 parts of alcohol, 0.1 to 0.5 parts of pH regulator, and 0.1 to 0.5 parts of preservative; Furthermore, the alcohol is at least one of ethylene glycol, 1,2-propylene glycol, and glycerol; the pH adjuster is at least one of triethanolamine, diethanolamine, ethanolamine, sodium bicarbonate, sodium hydroxide, sodium carbonate, sodium acetate, and ammonium bicarbonate; and the preservative is at least one of BIT, CMIT, and MIT.